Perspective on digital communication with health professions from close supporters of young people with long-term health conditions (The LYNC Study). (April 2022) - Temple, Ayako; Hamilton, Kathryn; Bryce, Carol; Griffiths, Frances; Sturt, Jackie
Objective: To understand the impact of digital communication using email and text between young people and their health care team on those in close supporting roles. Methods: Twelve people (nine parents and three partners) of young people with long-term health conditions were interviewed between November 2014 and March 2016. Thematic analysis was performed followed Braun and Clarke's (2006) 6-phase method. Results: Four main themes were identified. Close supporters felt that digital clinical communication was useful for young persons' self-management. As well as young patients, close supporters would also like to have direct access to the clinicians, but it was necessary to build up a trusting relationship between close supporters and clinicians initially. Video appointments were suggested for future digital communication technology. Conclusions: Close supporters were encouraging digital communication for their young person with diabetes. Clinicians should put an emphasis on establishing trusting relationships with both young people and close supporters which would be beneficial for their digital clinical communications.